Prihodnost zimskega turizma na Planini pod Golico v luči globalnega segrevanja - Ogrin, Matej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Warmer winters have brought the ski area Španov vrh near Jesenice in decline. New climate conditions put plans of conventional ski tourism in a different point of a view. The article analysis trends of air temperature and snow conditions in winter months at Planina pod Golico to find out if weather conditions assure development of classical winter tourism at ski area Španov vrh. As alternative to conventional way of tourism, the article recommends some new, more sustainable solutions for development of tourism, which could bring renaissance to Planina pod Golico.
Keywords: climate changes; climatogeography; geography of tourism; klimatogeografija; klimatske spremembe; Planina pod Golico; skiing; Slovenia; Slovenija; smučanje; sonaravni razvoj; sustainable development; tourism; turistična geografija; turizem; vlpivi; winter tourism; zimski turizem